2009
DOI: 10.1371/journal.ppat.1000430
|View full text |Cite
|
Sign up to set email alerts
|

Atg5-Independent Sequestration of Ubiquitinated Mycobacteria

Abstract: Like several other intracellular pathogens, Mycobacterium marinum (Mm) escapes from phagosomes into the host cytosol where it can polymerize actin, leading to motility that promotes spread to neighboring cells. However, only ∼25% of internalized Mm form actin tails, and the fate of the remaining bacteria has been unknown. Here we show that cytosolic access results in a new and intricate host pathogen interaction: host macrophages ubiquitinate Mm, while Mm shed their ubiquitinated cell walls. Phagosomal escape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 50 publications
(73 reference statements)
2
111
0
Order By: Relevance
“…How does this pathogen then enter the host vesicle trafficking system to ultimately exit via apical exocytosis? Recently, the autophagy pathway, which can be used to control intracellular pathogen growth, has been implicated as a "recapture" mechanism to return bacterial pathogens that have escaped into the cytoplasm back into a host endosome (39,40). However, our data indicate that the autophagy pathway is not important for N. parisii maturation and exit (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…How does this pathogen then enter the host vesicle trafficking system to ultimately exit via apical exocytosis? Recently, the autophagy pathway, which can be used to control intracellular pathogen growth, has been implicated as a "recapture" mechanism to return bacterial pathogens that have escaped into the cytoplasm back into a host endosome (39,40). However, our data indicate that the autophagy pathway is not important for N. parisii maturation and exit (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…We propose that the sudden and substantial increase in ALIS formation during inflammation is followed by rapid dynamics of their clearance that might be more efficiently handled directly by lysosomes. In this context, recent studies have suggested autophagy-independent lysosomal clearance of ubiquitinated Mycobacterium marinum (46) and mitochondria during reticulocyte maturation (47). It could be further argued that autophagy would be an ill-suited mechanism for ALIS clearance.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44] However, since Mtb is still detected in vesicle structures 16 h after infection (ref. 44 and data not shown) when autophagy block is already fully visible, it is likely that the effect on autophagy was not exerted by cytosolic Mtb.…”
Section: Methodsmentioning
confidence: 99%